Pola Interaksi Dosen-Mahasiswa dan Keterlibatan Akademik: Dinamika Universitas - Adesegun Olayide Odutayo; Udeme Samuel Jacob; Oluwaseyi Aina Gbolade Opesemowo; Habeeb Omoponle Adewuyi (Journal of Education and Teaching (JET), 2024)
Interactions within the classroom are essential since a conducive learning atmosphere is necessary. This study explored the relationship between lecturer-teacher interactions and learning effectiveness at universities. The survey design used in this study was correlational research design. The participants in this study were selected from universities in Kwara State. Using multi-stage sampling approaches, 350 student-teachers participated in the study. Proformas and a questionnaire designed by the researchers titled “Teacher-Student Interaction Questionnaire” were utilized to gather data. A split-half approach was utilized to determine the questionnaire’s reliability, and the gathered data was analyzed using Cronbach Alpha, which has a reliability coefficient of 0.78.Mean was used to answer the research questions, and the PPMC and t-test at the 0.05 significant level were used to test the hypotheses. According to the study’s findings, lecturer-teacher interactions in universities in Ilorin are not often vertical, antagonistic, authoritarian, or laissez-faire. This study also reported that most respondents had above-average academic engagement levels in Ilorin. The researchers recommended that lecturers prioritise building positive relationships with their students. Establishing trusting, supporting relationships with their students fosters open communication and a sense of trust that increases student engagement and motivation, which is why lecturers should prioritise developing these relationships.